2016
DOI: 10.1002/jmri.25461
|View full text |Cite
|
Sign up to set email alerts
|

Oximetric angiosome imaging in diabetic feet

Abstract: Purpose-To develop a noncontrast oximetric angiosome imaging approach to assess skeletal muscle oxygenation in diabetic feet.Materials and Methods-In four healthy and five subjects with diabetes, the feasibility of foot oximetry was examined using a 3T clinical magnetic resonance imaging (MRI) scanner. The subjects' feet were scanned at rest and during a toe-flexion isometric exercise. The oxygen extraction fraction of skeletal muscle was measured using a susceptibility-based MRI method. Our newly developed MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Although without comparable and homogeneous design between series (inclusion-exclusion criteria), these studies however revealed few changes in angiosome-oriented (DR versus IR) tissue capillaries during the early stages of revascularization [21] [22] [73]. Ostensibly, these findings about the World Journal of Cardiovascular Diseases progression of capillary reperfusion after DR/WTR appear to contradict similar research by Iida et al [6] by Shiraki et al [51] by Zheng et al [74] by Kawanishi et al [75] and by Okamoto et al [76] In a systematic literature review of 1290 CLTI cases, Biancari et al [78] found that DR may enhance superior wound healing rates, if this strategy can be technically applied [78]. In the same analysis, DR limb salvage rates were, however, comparable to IR but with no statistical weight [78].…”
Section: Current Literature Review Concerning Dr/wtr Strategiesmentioning
confidence: 85%
“…Although without comparable and homogeneous design between series (inclusion-exclusion criteria), these studies however revealed few changes in angiosome-oriented (DR versus IR) tissue capillaries during the early stages of revascularization [21] [22] [73]. Ostensibly, these findings about the World Journal of Cardiovascular Diseases progression of capillary reperfusion after DR/WTR appear to contradict similar research by Iida et al [6] by Shiraki et al [51] by Zheng et al [74] by Kawanishi et al [75] and by Okamoto et al [76] In a systematic literature review of 1290 CLTI cases, Biancari et al [78] found that DR may enhance superior wound healing rates, if this strategy can be technically applied [78]. In the same analysis, DR limb salvage rates were, however, comparable to IR but with no statistical weight [78].…”
Section: Current Literature Review Concerning Dr/wtr Strategiesmentioning
confidence: 85%
“…Previous clinical experience including our published research revealed that specific foot vascular territories with ischemic wounds may address different stages of atherosclerotic occlusive lesions of "source arteries" and appended collaterals 7,[34][35][36][37][38][39] , and belongs to a larger ongoing investigation regarding the anatomical and hemodynamic aspects of BTA vasculature in CLTI. Though doubts about the real clinical benefit of WDR for both bypass and EVT have been raised in contemporary literature 1-8, 10, 19-21, 32, 37 , using modern microcirculatory diagnostic methods with valuable topographic information 10,19,40,42 . While some authors have found the assessment of anatomical 6,10,16,28 and physiological 16,40,41 angiosomal flow by MRI oximetry 40 , trans-cutaneous laser Doppler 16,28 , or peripheral SPECT-Scan perfusion 10,[41][42][43] useful, others have questioned the utility of topographic reperfusion using white-light tissue spectrophotometry 44 , and low-frequency oscillations analyzed by diffuse speckle contrast analysis 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Though doubts about the real clinical benefit of WDR for both bypass and EVT have been raised in contemporary literature 1-8, 10, 19-21, 32, 37 , using modern microcirculatory diagnostic methods with valuable topographic information 10,19,40,42 . While some authors have found the assessment of anatomical 6,10,16,28 and physiological 16,40,41 angiosomal flow by MRI oximetry 40 , trans-cutaneous laser Doppler 16,28 , or peripheral SPECT-Scan perfusion 10,[41][42][43] useful, others have questioned the utility of topographic reperfusion using white-light tissue spectrophotometry 44 , and low-frequency oscillations analyzed by diffuse speckle contrast analysis 45 . The clinical value of all these studies that support or refute specific postoperative angiosomal microcirculatory changes is indisputable.…”
Section: Discussionmentioning
confidence: 99%